THE ROLE OF TRANSFORMATIONAL LEADERSHIP AND WORK CULTURE ON HUMAN RESOURCE PERFORMANCE WITH INTRINSIC MOTIVATION AS AN INTERVENING VARIABLE: A STUDY OF SERVICE COMPANIES IN PALEMBANG - Pratama, Deni; Fachrunnisa, Olivia (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research seeks to examine how transformational leadership and organizational culture affect human resource (HR) performance, with intrinsic motivation acting as a mediating factor in service companies in Palembang City. Using a quantitative explanatory approach, data were obtained from 64 respondents through a questionnaire and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The outcomes show that transformational leadership has a significant effect on intrinsic motivation, and intrinsic motivation has a significant impact on HR performance. However, work culture doesn’t have a significant impact on intrinsic motivation, and transformational leadership doesn’t directly have a significant impact on HR performance. Conversely, work culture has been shown to have a significant effect on HR performance. These findings reinforce the importance of building a strong organizational culture and maintaining intrinsic motivation as strategies to improve employee performance.